Análisis de igualdad de género y su incidencia en el ambiente laboral de los servidores públicos del GAD del cantón Bolívar - Carranza Delgado, María Carolina (2024)
The present study was developed in the Decentralized Autonomous Government (GAD) of the Bolívar canton, with the objective of analyzing the situation of gender equality among public servants of this institution, with a view to diagnosing and improving the work environment in terms of equity. To carry out the research, inductive, deductive and analytical research methods were used, complemented by data collection techniques such as interviews and surveys. An exhaustive bibliographic review was carried out to establish a solid legal basis that included guidelines on gender equality in the workplace of public entities. A regulatory framework composed of national and international provisions was consulted, so that GAD staff had immediate access to this information. The incidence of gender equality in the GAD of Bolívar was investigated by applying a survey to a sample representative of 169 workers and an interview with the director of the Human Talent Department. The results of the study revealed that the GAD of Bolívar does not have an institutional Action Plan that establishes strategic measures to promote the rights of public servants in the field of gender equality. Based on the findings of the study, the implementation of a comprehensive Action Plan for gender equity in the GAD Cantonal Bolívar is proposed to create a more fair and equitable work environment, promoting well-being and contributing to the improvement of institutional performance.